Analisis Manajemen Waktu Dan Biaya Menggunakan Metode Critical Path Method (CPM) Pada Proyek Gedung Rumah Hunian : (Studi Kasus Pembangunan Rumah 2 Lantai) - Pabidang, Wilson; Safari, Athiah; Syara, Elfiyusriningsi (CV. Shofanah Media Berkah, 2025)
Time management is an essential factor in the success of construction projects, as delays often lead to financial losses and reduced quality of work. Therefore, an appropriate method is needed for effective planning and control. One method that can be applied is the Critical Path Method (CPM), which is able to identify the critical path, project duration, and activities that must not be delayed. This study aims to analyze project time efficiency using CPM and to calculate direct costs based on the work volume derived from construction drawings using the Analisis Harga Satuan Pekerjaan (AHSP). The data used include the project schedule, activity durations, task dependencies, and work volumes. The analysis results show that the total project duration is 178 days, with the critical path consisting of mobilization, bowplank installation, earthwork, foundation, lean concrete, main structure, roofing, finishing, and final cleaning. All critical activities have no available float, meaning that any delay in one activity will affect the overall project duration. The direct project cost calculated using AHSP is Rp 1,478,634,218. Thus, the application of CPM proves useful in identifying critical activities, optimizing project scheduling, and providing a basis for decision-making to minimize delays in project implementation.